A double blinded prospective randomized trial comparing the effect of anatomic versus non-anatomic resection on hepatocellular carcinoma recurrence. Issue 8 (August 2017) - Feng, Xiaobin; Su, Yongjie; Zheng, Shuguo; Xia, Feng; Ma, Kuansheng; Yan, Jun; Li, Xiaowu; Tang, Wei; Wang, Shuguang; Bie, Ping; Dong, Jiahong
Abstract: Background: The aim of this study was to determine the effect of anatomic resection (AR) versus non-anatomic resection (NAR) on recurrence rates in patients with hepatocellular carcinoma (HCC). Methods: Eligible patients were randomized to AR or NAR from January 2006 to July 2007 at a single center. The primary outcome was the 2-year recurrence-free survival (RFS). Secondary outcomes were postoperative complications, time to first recurrence, 1-, 3-, and 5-year RFS, and overall survival (OS). Results: Fifty-three (51%) and 52 (50%) patients underwent NAR and AR, respectively. A larger proportion of patients achieved margins ≥20 mm in the AR group (52% vs. 30%; P = 0.023). Complications (blood loss, transfusion requirement, and hospital stay) were similar between the two groups. Median follow-up was 33 (range, 2–77) months. Incidence of local recurrence at 2 years was 30% and 59% in the AR and NAR groups, respectively. Median time to first local recurrence in the AR group was significantly longer than in the NAR group (53 vs. 10 months, P = 0.010). There was no difference in overall RFS between the two groups (P = 0.290). Discussion: AR decreased the 2-year local recurrence rate and increased the time to first local recurrence compared to NAR in patients with HCC.